Using cyanine dye J-aggregates as luminescence probe for nanostructured media - Sorokin, A.V.; Ropakova, I.Yu.; Borovoy, I.A.; Bespalova, I.I.; Yefimova, S.L. (Functional Materials, 2017)
Due to excitonic nature of electronic excitations in J-aggregates causing the unique spectral properties they successfully applied as luminescent probes in biology. In present report we demonstrate a possibility using J-aggregates as the probe for nanostructured materials basing on BIC J-aggregates. As the probing tool the exciton delocalization length has been used as well as the lifetime. It has been shown direct dependence of the exciton characteristics of the J-aggregates on the specific features of solid matrices such as nanoporous matrix and polymer films.